CISS-Based Label-Free Novel Electrochemical Impedimetric Detection of UVC-Induced DNA Damage - Bangruwa N.; Srivastava M.; Mishra D. (My University, 2025)
In this work, we demonstrate chiral-induced spin selectivity (CISS)-based label-free electrochemical impedimetric detection of radiation-induced DNA damage using the electrons' spin as a novel tool of sensing. For this, self-assembled monolayers (SAMs) of short ds-DNA (of length 7.14 nm) are prepared on arrays of multilayer thin film devices comprising a gold overlay (500 μm diameter with 10 nm thickness) on a nickel thin film (100 nm) fabricated by the physical vapor deposition technique. Subsequently, the SAMs of ds-DNA are exposed to ultraviolet C (UVC) radiation for a prolonged period of 8 h to induce structural perturbations in DNA. The susceptibility of DNA to radiation-induced damage was probed by recording the spin-dependent electrochemical impedimetric spectra, wherein a continuous sinusoidal wave of the amplitude of 10 mV was superimposed on DC bias in the frequency range of 100-105 Hz, with simultaneous spin injection through the attached DNA. The inherent correlation between the charge-transfer resistance (Rct) and the spin selectivity of electrons through DNA was taken into account for the detection of DNA damage for the first time with a limit of detection achieved up to 10 picomolar concentrations of DNA. As the spin-polarized electrons directly probe the structural symmetry, it is robust against perturbation from electronic signals usually found in conventional electrochemical biosensors. © 2016 American Chemical Society.